DERADIKALISASI ISTRI EKS NAPITER PADA YAYASAN GEMA SALAM SURAKARTA MELALUI PEMBERDAYAAN EKONOMI - Muhammad Irfan Syaifuddin; Diah Novita Fardani; Wakhid Musthofa (Yayasan Baitul Hikmah al-Zain, 2026)
This community service aims to help and empower women convicts in Karisedenan Surakarta in the economic field to start a village food and drink shop (angkringan) as a means to increase family income, socialize with the community, and mainly be part of the deradicalization program. For terrorist families who are then expected to be able to influence the husband of the perpetrator of the crime of terrorism who has moderate understanding and leaves radicalism, as well as a means of disengagement from terrorist networks because they already have business activities and return to their families. This service is carried out with a pattern of workshops and best practice entrepreneurship in food and beverage stalls aimed at the wives of convicts in the Karisedenan area of ​​Surakarta. Qualitative data analysis method through three activities, namely (1) data reduction, (2) data presentation, and (3) conclusion drawing and verification. The findings and results of the service targeting the wives and families of ex-terrorism convicts were that the participants were very enthusiastic and open to participating in service activities even though they were organized by a team from UIN Raden Mas Said Surakarta who had never previously collaborated with the Gema Salam Foundation Surakarta.